PRL-3 promotes telomere deprotection and chromosomal instability. Issue 11 (8th May 2017) - Lian, Shenyi; Meng, Lin; Yang, Yongyong; Ma, Ting; Xing, Xiaofang; Feng, Qin; Song, Qian; Liu, Caiyun; Tian, Zhihua; Qu, Like; Shou, Chengchao
Abstract: Phosphatase of regenerating liver (PRL-3) promotes cell invasiveness, but its role in genomic integrity remains unknown. We report here that shelterin component RAP1 mediates association between PRL-3 and TRF2. In addition, TRF2 and RAP1 assist recruitment of PRL-3 to telomeric DNA. Silencing of PRL-3 in colon cancer cells does not affect telomere integrity or chromosomal stability, but induces reactive oxygen species-dependent DNA damage response and senescence. However, overexpression of PRL-3 in colon cancer cells and primary fibroblasts promotes structural abnormalities of telomeres, telomere deprotection, DNA damage response, chromosomal instability and senescence. Furthermore, PRL-3 dissociates RAP1 and TRF2 from telomeric DNA in vitro and in cells. PRL-3-promoted telomere deprotection, DNA damage response and senescence are counteracted by disruption of PRL-3–RAP1 complex or expression of ectopic TRF2. Examination of clinical samples showed that PRL-3 status positively correlates with telomere deprotection and senescence. PRL-3 transgenic mice exhibit hallmarks of telomere deprotection and senescence and are susceptible to dextran sodium sulfate-induced colon malignancy. Our results uncover a novel role of PRL-3 in tumor development through its adverse impact on telomere homeostasis.